Enhanced and stabilized arsenic retention in microcosms through the microbial oxidation of ferrous iron by nitrate. (February 2016) - Sun, Jing; Chillrud, Steven N.; Mailloux, Brian J.; Stute, Martin; Singh, Rajesh; Dong, Hailiang; Lepre, Christopher J.; Bostick, Benjamin C.
Abstract: Magnetite strongly retains As, and is relatively stable under Fe(III)-reducing conditions common in aquifers that release As. Here, laboratory microcosm experiments were conducted to investigate a potential As remediation method involving magnetite formation, using groundwater and sediments from the Vineland Superfund site. The microcosms were amended with various combinations of nitrate, Fe(II)(aq) (as ferrous sulfate) and lactate, and were incubated for more than 5 weeks. In the microcosms enriched with 10 mM nitrate and 5 mM Fe(II)(aq), black magnetic particles were produced, and As removal from solution was observed even under sustained Fe(III) reduction stimulated by the addition of 10 mM lactate. The enhanced As retention was mainly attributed to co-precipitation within magnetite and adsorption on a mixture of magnetite and ferrihydrite. Sequential chemical extraction, X-ray absorption spectroscopy and magnetic susceptibility measurements showed that these minerals formed at pH 6–7 following nitrate-Fe(II) addition, and As-bearing magnetite was stable under reducing conditions. Scanning electron microscopy and X-ray diffraction indicated that nano-particulate magnetite was produced as coatings on fine sediments, and no aging effect was detected on morphology over the course of incubation. These results suggest that a magnetite based strategy may be a long-term remedial option for As-contaminated aquifers. Graphical abstract: Highlights: Magnetite is advantageous as the host-mineral for As immobilization. We conduct microcosms with sediment and groundwater from an As-contaminated site. We trace the evolution of water composition and sediment mineralogy concurrently. Addition of ferrous Fe and nitrate produces mineral assemblage including magnetite. The study represents an initial attempt to produce relatively stable As sequesters.